Relationship Between the Ozone and Water Vapor Columns on Mars as Observed by SPICAM and Calculated by a Global Climate Model. Issue 4 (20th April 2021) - Lefèvre, F.; Trokhimovskiy, A.; Fedorova, A.; Baggio, L.; Lacombe, G.; Määttänen, A.; Bertaux, J.‐L.; Forget, F.; Millour, E.; Venot, O.; Bénilan, Y.; Korablev, O.; et al.
Abstract: Ozone (O3 ) in the atmosphere of Mars is produced following the photolysis of CO2 and is readily destroyed by the hydrogen radicals (HOx ) released by the photolysis and oxidation of water vapor. As a result, an anti‐correlation between ozone and water vapor is expected. We describe here the O3 ‐H2 O relationship derived from 4 Martian years of simultaneous observations by the SPICAM spectrometer onboard the Mars Express spacecraft. A distinct anti‐correlation is found at high latitudes, where the O3 column varies roughly with the −0.6 power of the H2 O column. The O3 and H2 O columns are uncorrelated at low latitudes. To evaluate our quantitative understanding of the Martian photochemistry, the observed O3 ‐H2 O relationship is then compared to that predicted by a global climate model with photochemistry. For identical model and observed abundances of H2 O, the model underpredicts observed ozone by about a factor of 2 relative to SPICAM when using the currently recommended gas‐phase chemistry. Sensitivity studies employing low‐temperature CO2 absorption cross sections, or adjusted kinetics rates, do not solve this bias. Taking into account potential heterogeneous processes of HOx loss on clouds leads to a significant improvement, but only at high northern latitudes. More broadly, the modeled ozone deficits suggest that the HOx ‐catalyzed photochemistry is too efficient in our simulations. This problem is consistent with the long‐standing underestimation of CO in Mars photochemical models, and may be related to similar difficulties in modeling O3 and HOx in the Earth's upper stratosphere and mesosphere. Plain Language Summary: The thin ozone layer on Mars is produced when the solar ultraviolet light breaks the CO2 molecules that compose 95% of its atmosphere. Conversely, ozone on Mars is readily destroyed by the hydrogen species released by water vapor. An inverse relationship is therefore expected between the quantities of ozone and water vapor. Quantifying this relationship provides important insight into the hydrogen chemistry that stabilizes the composition of the Mars atmosphere. We describe here the ozone and water vapor measurements performed during 4 Martian years (7.5 Earth years) by the SPICAM instrument onboard the Mars Express spacecraft. We then attempt to reproduce these measurements with a Mars climate model with photochemistry. Although the model reproduces the inverse relationship observed between ozone and water vapor, the ozone amount is underestimated by about a factor of 2 in the simulations. The ozone deficit suggests that the destruction by hydrogen species is too strong when one uses the currently recommended reaction rates. This problem is consistent with the long‐standing underestimation in Mars models of carbon monoxide, also destroyed by hydrogen species, and can be related to similar difficulties in modeling ozone in the Earth's upper atmosphere. Key Points: The relationship between the O3 and H2 O columns on Mars is quantified from 4 Martian years of simultaneous measurements The O3 and H2 O columns are distinctly anti‐correlated at high latitudes but are uncorrelated at low latitudes Model simulations using the observed amount of H2 O and the currently recommended kinetics underpredict O3 by about a factor of 2